Influence of Certain Nutritional Products On Periodontal Status - Urim, Tefiku; Mirjana, Popovska; Amella, Cana; Zendeli Bedxeti, Lindita; Bilbil, Recica; Spasovska-Gjorgovska, Ana; Spasovski, Spiro (European Scientific Journal, ESJ, 2022)
Material and Method: 60 patients within the age range of 35-65 years were included. The selection of the respondents was made by a simple random method. As a criterion in the research sample, the depth of the periodontal pockets was taken into account, which was from 3 to 5 mm, according to which a selection was made. Chronic periodontal disease with a clinically manifest stage was diagnosed in all patients. Each of the respondents had the opportunity to estimate the frequency of personal consumption of 6 selected food items (vegetables, fast food, fish, meat, fruits, and desserts) by choosing one of three possible answers (never, infrequently and often consumed). For the clinical part of the study, 4 parameters were measured, namely: GI-gingival inflammation, PI-plaque index, PPD-depth of periodontal pockets, and CAL-clinical loss of attachment. The findings were statistically processed. Results: For the male and female respondents, the average age was 39.8 ± 5.3 with min/pop of 30/53 years and 41.2 ± 6.3 with min / pop of 32/55 years, respectively. The analysis showed that, for p> 0.05, the frequency of consumption of vegetables significantly decreased, and the consumption of fast food insignificantly increased the values of the four clinical parameters (GI, PI, PPD, CAL). Conclusion: Consumption of fish, meat, and vegetables reduces the values of clinical parameters (PI, GI, PPD, CAL). This is in contrast to fast food and dessert which indicated an increase in the values of PPD and CAL.